Anti-N-Methyl-D-Aspartate Receptor Encephalitis: Response to Early Treatment - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2010)
A 5-year-old girl with anti-N-methyl-D-aspartate (NMDA) receptor encephalitis and near-complete recovery following early diagnosis and treatment with immune globulin and steroids is reported from Indiana University, University of Pennsylvania, and Mayo Clinic.